Home security [ (San Fransisco : Digital Entertainment International, 2007)
The DIY DVD range is the step essential step by step to follow visual aid fir any DIY enthusiast.Each DVD reveals handy tips from the trade and gives professional instruction on how to carry out home improvements, repairs and maintenance
1. Fitting a cylinder lock -- 2. Fitting a mortice lock -- 3. Fitting hinge lock -- 4. Fitting window lock -- 5.Fitting door bolts -- 5. Fitting a door chain -- 6. Handy hints
Keywords: Dwellings -- Maintenance and repair; Security Measures